Adsorption of sunflower oil pigments on the diatomite surface - Y. A. Ubaskina; Y. A. Korosteleva (Новые технологии)
The article is devoted to the adsorption of sunflower oil pigments on the surface of protonated diatomite. It is found that the degree of extraction of β-carotene from the oil by protonated diatomite depends mainly on the amount of adsorbent, and the degree of extraction of chlorophyll A depends on the magnitude of the positive charge of the surface of the protonated diatomite, which increases with the addition of 1 mass % of aluminum hydroxide.